Fibre Reinforced Plastic Composites: Kenaf (Hibuscus Cannabunus.L.) Fibre- Polypropylene Blend - Tan, Khim Seong (2002)
This study aimed to evaluate the chemical compositions, analytical and Mechanical properties of Kenaf (Hibiscus cannabinus, L.) fibres blended with polypropylene at various fibre loading and fibre length. The effects of electron beam irradiation at dose 10 kGray and 1% maleated polypropylene (MAPP) on this composite were also investigated. Kenaf stalks with the age of 4 months obtained from MARDI, Serdamg were defibrated with two types of processing method, namely wet atmospheric pressurized refiner mechanical pulping (RMP) and dry hammermill process. The fibres and particles from these two processes were oven dried and screened into three different sizes: 1-2 mm, 0.5-1 mm, and <0.5 mm. Fibres with length between 0.5-1 mm were used for chemical analysis process. Results showed that kenaf fibre has higher cellulose and lower lignin content than rubber wood fibre. The ash content of kenaf fibre was also lower than empty fruit brunch.